2021
DOI: 10.1177/17588359211039047
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib for patients with metastatic biliary tract carcinoma refractory to standard chemotherapy: results from an investigator-initiated, open-label, single-arm, exploratory phase II study

Abstract: Background: There is no standard therapy for metastatic biliary tract carcinoma (BTC) refractory to first-line chemotherapy. Apatinib, a VEGFR2 tyrosine kynase inhibitor, showed an activity against BTC xenografts in preclinical models. We conducted an exploratory study to evaluate the efficacy and safety of apatinib in patients with metastatic BTC. Methods: This is a single-arm phase II study [ClinicalTrials.gov identifier: NCT03427242]. Eligible patients were aged 18 years or older; histologically confirmed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…e literature [21] showed that gemcitabine, oxaliplatin, and apatinib significantly improved the shortand long-term outcomes and reduced the incidence of adverse effects in patients with biliary cancer. is finding is consistent with a previous study by [22] et al Improved treatment outcomes and increased overall survival time have been shown in patients with gallbladder cancer in a manner that is both very safe and within the tolerable range of possible side effects [23]. ere are certain limitations in this study, mainly including limited sample size, deviation of the study results from actual clinical data, which affects the reliability of the study report; insufficient time to assess the long-term effectiveness and resistance to treatment; and failure to consider the effects of drug treatment on other immune mechanisms.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…e literature [21] showed that gemcitabine, oxaliplatin, and apatinib significantly improved the shortand long-term outcomes and reduced the incidence of adverse effects in patients with biliary cancer. is finding is consistent with a previous study by [22] et al Improved treatment outcomes and increased overall survival time have been shown in patients with gallbladder cancer in a manner that is both very safe and within the tolerable range of possible side effects [23]. ere are certain limitations in this study, mainly including limited sample size, deviation of the study results from actual clinical data, which affects the reliability of the study report; insufficient time to assess the long-term effectiveness and resistance to treatment; and failure to consider the effects of drug treatment on other immune mechanisms.…”
Section: Discussionsupporting
confidence: 94%
“…The literature [ 21 ] showed that gemcitabine, oxaliplatin, and apatinib significantly improved the short- and long-term outcomes and reduced the incidence of adverse effects in patients with biliary cancer. This finding is consistent with a previous study by [ 22 ] et al Improved treatment outcomes and increased overall survival time have been shown in patients with gallbladder cancer in a manner that is both very safe and within the tolerable range of possible side effects [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“… 11 In a systematic review of second‐line chemotherapies, which included 761 patients and 25 trials, mean PFS, OS, and ORR were merely 3.2 months, 7.2 months, and 7.7%, respectively. 28 Monotherapy with antiangiogenic TKIs, including regorafenib and apatinib, also yielded minimal efficacy in pretreated advanced BTCs, with median OS of 5.3 and 4.81 months, 29 , 30 respectively. As for ICI monotherapy, existing findings on second‐line use of programmed cell death protein 1 (PD‐1)/PD‐L1 inhibitors in BTCs are controversial, with a discrepancy in median OS ranging from 5.2 to 14.24 months.…”
Section: Discussionmentioning
confidence: 99%